2007
DOI: 10.1021/es0702622
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Hexabromocyclododecane at an Industrial Plant

Abstract: Occupational exposure to hexabromocyclododecane (HBCD) among workers at an industrial plant producing expandable polystyrene (PS) added HBCD as flame retardant has been assessed in the present study. Airborne dust samples were collected near the breathing zone of 10 male workers during three 8-h work shifts. The HBCD concentrations in the airborne dust varied from 0.2 to 150 microg/m3 (mean 12.2 and median 2.1 microg/m3). Two serum samples were obtained from each of the workers. The mean serum concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 24 publications
3
64
1
2
Order By: Relevance
“…These results indicated that birds did not show clear preference for one or the other a-HBCD enantiomer. This phenomenon was also observed in marine species from the Western Scheldt Estuary and in human samples (Thomsen et al, 2007;Eljarrat et al, 2009;Abdallah and Harrad, 2011). Since most of previous studies did not simultaneously determine the enantiomeric fractions of HBCD isomers in both biota and their food, the observed nonracemic distribution of HBCD isomers could not simply be contributed to enantioselective uptake, metabolism, and/or excretion of HBCD in biota.…”
Section: Enantiomeric Fractions Of Hbcdmentioning
confidence: 61%
“…These results indicated that birds did not show clear preference for one or the other a-HBCD enantiomer. This phenomenon was also observed in marine species from the Western Scheldt Estuary and in human samples (Thomsen et al, 2007;Eljarrat et al, 2009;Abdallah and Harrad, 2011). Since most of previous studies did not simultaneously determine the enantiomeric fractions of HBCD isomers in both biota and their food, the observed nonracemic distribution of HBCD isomers could not simply be contributed to enantioselective uptake, metabolism, and/or excretion of HBCD in biota.…”
Section: Enantiomeric Fractions Of Hbcdmentioning
confidence: 61%
“…Enantioselective analysis was also performed and (-)α-HBCDD was identified as the dominant enantiomer. Thomsen et al (2007) investigated serum HBCDD concentrations of 10 workers at an industrial plant producing expandable polystyrene with added HBCDDs as a flame retardant. Two serum samples were collected for each worker: first sampling was performed during the first production period and the second sampling about 6 weeks after the end of the manufacturing of the HBCDD-containing products.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…This is seven times higher than the mean HBCD concentration (12.2 μg m −3 ) in the air of an industrial plant producing EPS. 12 HBCD concentrations in outdoor air near potential point sources in Sweden were in the range of 0.013−1070 ng m −3 . 11 The same study also showed the presence of HBCD in air from urban environments at the in public microenvironments.…”
Section: −1mentioning
confidence: 99%
“…6,7 In view of the environmental persistence and the adverse health effects of HBCD, studies have attempted to elucidate the sources of HBCD. Some sources, such as HBCD production, 10 polystyrene foam production, 11,12 municipal dumping sites, 13 and ewaste recycling, 14 have been identified. Also, HBCD has been found in indoor air and dust, most likely being released from indoor sources such as furniture foams, electric equipment, and textile coatings.…”
Section: ■ Introductionmentioning
confidence: 99%